DISCIPLINE AS A SOCIAL EVENT AND PEDAGOGICAL PROCESS: THE STATUTE OF PRE - SCHOOL EDUCATION IN UZBEKISTAN AND THE ROLE OF IT IN BRING UP KIDS - Ibroximova Maloxatbonu,; Karimova Gulsanam,; Solomboyeva Oʻgʻiloy,; Mamadaliyeva Xabiba, (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA'LIMNING INNOVATSION YO'NALISHLARI, 2025)
Discipline in early childhood is a crucial social and pedagogical phenomenon that shapes children’s behavior, social skills, and readiness for formal education. This article explores discipline as both a social event and a pedagogical process within the framework of the Pre-School Education Statute in Uzbekistan. It examines the legislative foundations of pre-school education, the role of discipline in the upbringing of children, and how these elements contribute to the holistic development of young learners. The study highlights the importance of culturally sensitive and developmentally appropriate discipline strategies to foster positive socialization and learning outcomes.